Trace of molecular doping in metal–organic frameworks: drastic change in the electronic band structure with a preserved topology and porosity. Issue 25 (12th June 2020) - Liu, Hai-Xiong; Liu, Ting-Ting; Huang, Tao; Fang, Zhi-Bin; Li, Lan; Yin, Qi; Cao, Rong; Gong, Xue-Qing; Liu, Tian-Fu
Abstract : The band gap of MOFs was engineered through molecular doping. The new method is applicable to various types of MOFs and dopants, presenting an easy and general strategy to broaden the potential application scope of MOF materials. Abstract : Doping, introducing traces of impurity into a material to alter its original electrical or optical properties, constitutes the fundamental basis for a number of electronic devices that are used in materials science. In this study, we demonstrate that doping trace amounts of organic molecules into metal–organic frameworks (MOFs) dramatically alters the electrical structure and optical property of the bulky material without disturbing the original frameworks, as confirmed by both powder and single-crystal X-ray diffraction. This method is applicable to various dopants and different types of MOFs. Theoretical calculations suggested that the dopant introduces an impurity level in the host band structure, which considerably narrows the band gap and increases the photogenerated electron–hole separation. Therefore, photocatalytically inert MOFs can achieve excellent activity for water splitting into hydrogen through molecular doping. The findings presented here provide a powerful yet facile strategy toward regulating the electronic band structure of MOFs for improved catalytic activity without necessarily changing the original chemical components, topology, and porosity.